Machine-learning based strategy identifies a robust protein biomarker panel for Alzheimer’s disease in cerebrospinal fluid - Xiaosen Hou; Yunjie Qiu; Hui Li; Yan Yan; Dongxu Zhao; Simei Ji; Junjun Ni; Jun Zhang; Kefu Liu; Hong Qing; Zhenzhen Quan (Alzheimer’s Research & Therapy)
Abstract Background The complex pathogenesis of Alzheimer’s disease (AD) has resulted in limited current biomarkers for its classification and diagnosis, necessitating further investigation into reliable universal biomarkers or combinations. Methods In this work, we collect multiple CSF proteomics datasets and build a universal diagnose model by SVM-RFECV method combined with equal sample size and standard normalization design. The model was training in 297_CSF and then test the effect in other datasets. Results Utilizing machine learning, we identify a 12-protein panel from cerebrospinal fluid proteomic datasets. The universal diagnosis model demonstrated strong diagnostic capability and high accuracy across ten different AD cohorts across different countries and different detection technologies. These proteins involved in various biological processes related to AD and shows a tight correlation with established AD pathogenic biomarkers, including amyloid-β, tau/p-tau, and the Montreal Cognitive Assessment score. The high accuracy in the model may due to multiple protein combination based on comprehensive pathogenesis and different AD progress. Furthermore, it effectively differentiates AD from mild cognitive impairment (MCI) and other neurodegenerative disorders, especially the frontotemporal dementia (FTD), which share similar pathogenesis as AD. Conclusion This study highlights a high accuracy, robustness and compatibility model of 12-protein panel whose detection is even based on label-free, TMT and DIA mass spectrometry or ELISA technologies, implicating its potential prospect in clinical application.